2022
DOI: 10.5713/ab.21.0145
|View full text |Cite
|
Sign up to set email alerts
|

Blood biochemical parameters and organ development of brown layers fed reduced dietary protein levels in two rearing systems

Abstract: Objective: An experiment was conducted to evaluate the effect of different levels of crude protein (CP) and two rearing systems (cage and floor), on blood parameters and digestive and reproductive organ development of brown laying hens.Methods: A total of 400 Hisex Brown laying hens between 30 and 45 weeks of age were distributed in a completely randomized design and a 2×4 factorial arrangement, with main effects including two rearing systems (cage and floor) and levels of CP (140, 150, 160, and 180 g/kg), in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 32 publications
(34 reference statements)
0
1
0
Order By: Relevance
“…Various studies have investigated this relationship. Viana et al (2022) evaluated the effect of different levels of crude protein and 2 rearing systems (cage and floor) on the blood parameters and organ development of brown laying hens. The study found that blood parameters were similar in birds reared in both cage and floor systems.…”
Section: Introductionmentioning
confidence: 99%
“…Various studies have investigated this relationship. Viana et al (2022) evaluated the effect of different levels of crude protein and 2 rearing systems (cage and floor) on the blood parameters and organ development of brown laying hens. The study found that blood parameters were similar in birds reared in both cage and floor systems.…”
Section: Introductionmentioning
confidence: 99%